An Active of Extracellular Cellulose Degrading Enzyme from Termite Bacterial Endosimbiont - M. Saifur Rohman; Endang Pamulatsih; Yudi Kusnadi; Triwibowo Yuwono; Erni Martani (Indonesian Journal of Biotechnology, 2015)
Cellulase is an ezyme that specifically cleaves the 1,4-β-glycosidic bond of cellulose to produce thesmall fragments of simple carbohydrate. This work was aimed to characterize the extracellular cellulase fromPaenibacillus spp., which was previously isolated from macro termites, Odontotermes bhagwatii in our laboratory.Two Paenibacillus isolates were used in this experiment, namely Paenibacillus cellulositrophicus SBT1 andPaenibacillus, sp. SBT8. Analysis of the total proteins in the supernatants showed that P. cellulositrophicus SBT1and Paenibacillus sp. SBT8 roughly produced as much as 18.6 mg/l and 24.8 mg/l of extracellular cellulases,respectively. Enzymatic assay showed that SBT1 and SBT8 cellulase exhibited enzymatic acitivity of 0.17 U/mg and 0.12 U/mg, respectively. Temperature dependencies analysis indicated that both cellulases exhibitedmaximum activity at 35oC. At the temperature higher than 55oC, the enzymatic activities of both cellulases wereroughly 20% reduced compared to the maximum activity. SBT1 and SBT8 cellulases were both active at acidicpH. At basic pH (pH 8) the enzymatic activities of both cellulases were reduced roughly 30% compared to thatof acidic pH. Supplementing of Mg2+, Zn2+, and Ca2+ in range of 1-10 mM increased the enzymatic activity ofboth cellulases roughly 33 to 50%.